A pretensão a uma mera providência jurisdicional baseada em cognição sumária: a relevante utilidade da tutela antecipada antecedente - Pinho, Américo Andrade (2021)
The judicial adjudication process based on full and exhaustive cognition cannot be understood, exclusively, as the one that tends to deliver a merit decision that can be covered by res judicata, since the evolution of procedural science allows to consider other models of process. The citizen's interest, in exercising his fundamental right to legal protection provided by the State, may be to obtain the certification of the existence of his right, but he can also turn only to the factual plan, in order not to obtain a judicial declaration on the contested right, but rather to benefit from a “mere” jurisdictional measure, thus understood as the prompt intervention of the judge in the factual world, precipitating effects that would result from a final sentence. It is investigated in this research if, as in the procedural systems of other countries, the stabilization of the antecedent preliminary injunction (introduced by the Brazilian Civil Procedure Code 2015) can fulfill this role, based on summarized cognition but without neglecting the necessary consideration of the constitutional principle of the adversary. There are the main contours of the entire system of provisional tutelage and the approximation of stabilization with monitoring tutelage. When dealing with the civil procedural law of an essentially instrumental science, connected with practice, controversial issues are addressed, linked to the application of the institute, which must be addressed in order not to compromise the acceptance of the stabilization of preliminary injunction by the legal community, with its potential to serve the development of Brazil's civil justice system